Microbial Flow Within an Air-Phyllosphere-Soil Continuum - Zhou, Shu-Yi-Dan; Li, Hu; Giles, Madeline; Neilson, Roy; Yang, Xiao-ru; Su, Jian-qiang (Frontiers in Microbiology, 2021)
The phyllosphere is populated by numerous microorganisms. Microbes from the wider environment, i.e. air and soil, are considered key contributors to phyllosphere microbial communities, but their contribution is unclear. This study seeks to address this knowledge gap by controlling the movement of microbes along an air-phyllosphere-soil continuum. A customized equipment with dual chambers was constructed that permitted airflow to enter the first chamber while the second chamber recruited filtered microbe-free air from the initial chamber. Allium schoenoprasum (chive) and Sonchus oleraceus (sow thistle) were cultivated in both chambers and the microbial communities from air, phyllosphere and soil samples were characterized. Shared of microbial OTUs in the equipment suggested a potential interconnection between the air, phyllosphere and soil system. Fast expectation-maximization microbial source tracking (FEAST) suggested that soil was the major source of airborne microbial communities. In contrast, the contribution of airborne and soil microbes to phyllosphere microbial communities of either A. schoenoprasum or S. oleraceus was limited. Notably, the soilborne microbes were the only environmental sources to phyllosphere in the second chamber, and could affect the composition of phyllosphere microbiota indirectly by air flow. The current study demonstrated the possible sources of phyllosphere microbes by controlling external airborne microbes in a designed microcosm system, and provided a potential strategy for recruitment for phyllosphere recruitment.